1996
DOI: 10.1148/radiology.200.1.8657900
|View full text |Cite
|
Sign up to set email alerts
|

MR sialography. Work in progress.

Abstract: Preliminary work indicates that this MR technique can successfully demonstrate both normal and abnormal parotid and submandibular gland duct systems and has several advantages over conventional x-ray sialography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 0 publications
0
38
0
4
Order By: Relevance
“…The findings are tabulated in the table 1. Lomas et al 18 presented case reports of n=3 patients in which MRS added additional information for calculus. The results of the above study are however not representative of the patient population since there was a sample selection bias due to the representation of only n=3 cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings are tabulated in the table 1. Lomas et al 18 presented case reports of n=3 patients in which MRS added additional information for calculus. The results of the above study are however not representative of the patient population since there was a sample selection bias due to the representation of only n=3 cases.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound has been recommended as first line of investigation by Alyas et al 16 and Katz et al 17 but again its use is limited due to operator dependency. The use of MR Sialography (MRS) has been stated by Lomas et al 18 which reported the successful use of MRS for evaluation of salivary glands. Tonami et al 19 and Gadodia et al 14 suggested that MRS has the advantage of revealing both the ductal and parenchymal changes along the salivary glands without exposure to radiation.…”
Section: Njr I Vol 1 I No 1 I Issue 1 I July-dec 2011mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides traditional sialography, sonography, CT scan, and MRI, new techniques such as MR sialography 26,27 and sialoendoscopy 28 are now available. By providing a preoperative diagnosis, those techniques may help in treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 MR sialography with heavily T2-weighted images is considered a new and promising technique that will probably replace standard sialography. 26,27 The most recent diagnostic and interventional technique is sialoendoscopy, which is probably one of the most reliable procedures to provide information on salivary duct diseases. 28 The sialendoscope with a working channel for instrumentation permits the introduction of a biopsy forceps to obtain tumor tissue for preoperative diagnosis.…”
Section: Discussionmentioning
confidence: 99%